Aliran-aliran Islam Kontemporer di Indonesia - Prayetno, Eko; Mubaraq, Zulfi; Nur, Ahmad Kholil; Al-Ghatnaini, Raed Awadh Saeed; Saelaemae, Tasnim (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2024)
Islam's development in Indonesia has been shaped by both positive and negative influences. On the positive side, technology, modernization, and globalization have supported the spread and evolution of Islamic thought. However, challenges include the lasting impact of the Abbasid Dynasty's decline, psychological issues among Muslims, and the rise of religious identity politics. Overall, contemporary Islamic sects bring new perspectives, demonstrating how Islam adapts to modernity and is influenced by both local and global dynamics. (content analysis) Miles and Huberman models. The results found 3 things: First, the paradigm of Contemporary Islamic Sectss in Indonesia has 7 forms: Determinism Sects of thought, Liberalism Sects of thought, Contemporary Islamic Sects of thought, Fundamentalist Sects of thought, Modernism Sects of thought, extremism movement Sects, rational religious Sects Second, internally influencing Contemporary Islamic Sectss in Indonesia there are 3 factors positive influence and negative influence, influence of ijtihad ulama, influence of scientific epistemology As for externally influencing Contemporary Islamic Sects in Indonesia there are 3 factors The influence of capitalist economy, The influence of Islamisation, The influence of pragmatism Third, the positive implications of Contemporary Islamic Sectss in Indonesia. Islam's development in Indonesia has been shaped by both positive and negative influences. On the positive side, technology, modernization, and globalization have supported the spread and evolution of Islamic thought.